Construcciones y performances : las prendas de Alicia Framis - Páez, Montserrat López (2017)
The article proposes the incorporation of the way of doing in Framis’s art in the area of the artistic research, by its specificity. The artist combines traditional and new media art, communication and visual culture, to elaborate their projects: series of improbable constructions, ephemeral architecture or installations and clothing, at the service of a performative purpose. The unusual constructions captivate the public and propitiate in him new experiences from where being able to adopt new perspectives and reflections on some of many irresolute social questions